Promotion of forest owner cooperatives in Lithuania : policy strategies to facilitate sustainable forest management - Hansen, Torben (SLU/Southern Swedish Forest Research Centre, 2013)
Forest owner cooperatives are often regarded as a policy vehicle to improve the management of private forests and facilitate entrepreneurship in the forest sector. This can be especially important for countries with economies in transition and recently restored private forest ownership. This study provides decision support and policy recommendations for the promotion of forest owner cooperatives in Lithuania. General characteristics of forest owner cooperatives and cooperative entrepreneurship are portrayed as well as the situation in private forestry in Lithuania. International case studies on forest owner cooperatives and public policies in their regard serve to derive elements and aspects of cooperation that are applicable elsewhere as well as concrete policy recommendations for the case of Lithuania. A variety of different entrepreneurial approaches of existing forest owner cooperatives is found to be applicable to Lithuania as well as different policy measures to promote them. Preferably a policy framework consisting of a complementary mixture of public services and financial support should be chosen for the Lithuanian case and implemented with sufficient financial and personnel capacity in order to achieve an effective policy impact. Thus the promotion of forest owner cooperatives holds much potential to improve the viability and sustainability of private forest management in Lithuania.